2018
DOI: 10.3892/mmr.2018.8538
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of miR-27b in the development of gastric cancer

Abstract: Previous studies have demonstrated that microRNAs (miRNAs/miRs) act as tumor suppressors or oncogenes during multiple processes in cancer. It has been observed that miR-27b may act as a tumor-suppressor and was significantly downregulated in a number of types of cancer. However, the functions of miR-27b in gastric cancer (GC) remain unclear. The present study aimed to investigate the functional role of miR-27b in the progression of GC. The downregulation of miR-27b in human GC plasma was confirmed using miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Current research to a certain extent supports this hypothesis, as Pan et al reported overexpression of ZFAS1 in gastric cancer (GC) serum and tissue samples and demonstrated that ZFAS1 knockdown inhibits the proliferation and migration of GC cells by suppressing cell cycle progression and apoptosis [150], while Chen et al demonstrated that miR-27b is downregulated in GC and show miR-27b to be a potential GC biomarker. Moreover, they show that miR-27b functions as a tumor suppressor in GC by targeting VEGFC [151]. This shows a possible inverse relationship between ZFAS1 and miR-27b.…”
Section: Hypothesis 3: Zfas1 May Play a Role In The Fine-mentioning
confidence: 88%
“…Current research to a certain extent supports this hypothesis, as Pan et al reported overexpression of ZFAS1 in gastric cancer (GC) serum and tissue samples and demonstrated that ZFAS1 knockdown inhibits the proliferation and migration of GC cells by suppressing cell cycle progression and apoptosis [150], while Chen et al demonstrated that miR-27b is downregulated in GC and show miR-27b to be a potential GC biomarker. Moreover, they show that miR-27b functions as a tumor suppressor in GC by targeting VEGFC [151]. This shows a possible inverse relationship between ZFAS1 and miR-27b.…”
Section: Hypothesis 3: Zfas1 May Play a Role In The Fine-mentioning
confidence: 88%
“…Numerous studies have revealed the relationship between miR-27b-5p and gene expression. Chen et al observed that miR-27b inhibited cell proliferation and induce apoptosis in gastric cancer cells [33]. Wu et al demonstrated that lncRNA ZEB2-AS1 promoted tumorigenesis and development of bladder cancer through down-regulating tumor-suppressive miR-27b [34].…”
Section: Discussionmentioning
confidence: 99%
“…Among altered miRNAs in patients, we found that miR-27b is remarkedly increased in liver tissue and serum from the early phase of NAFLD to severe NASH [12,13]. It has been reported that miR-27b is involved in cell proliferation, differentiation, migration, invasion, metastasis, multi-drug resistance in various tumor cells [14][15][16][17][18]. However, the exact role of miR-27b in NAFLD pathogenesis, and in particular its relationship to adipocyte differentiation, remains unclear.…”
Section: Introductionmentioning
confidence: 99%